Assessment of the domesticity, flexibility, and user involvement of the community-driven housing in the Philippines - Royo, Jairo Christian N.; Juanga, Jean Marie V. (2020)
The study aimed to seek the basic composition of Filipino domestic interiors, in the context of the low-income, community-driven, urban poor communities across the Philippines. As urban population continue to inflate, arable lands for habitation experience the opposite. Contemporary mass housing is standardized to the bare minimum in order to be cost and space efficient. In return, discomfort and dissatisfaction of the end-users with their limited house units is apparent, since these do not respond to their diurnal domestic activities. Assessing the domestic spatial characteristics, composition, and the phenomenon of flexibility in the community-driven houses provides progressive contextualization of domestic spaces in housing. These houses mobilized by the Philippine Alliance involves user participation in the creation of these houses. Thus, having the end-users participate in the design and planning phase generates a strong participatory component influencing the creation of their interior spaces, and their total satisfaction toward their units. A combination of quantitative and qualitative method was implored in gathering the data, synthesizing the results, and the interpretation of the data. The data was collected and obtained thru self-administered structured survey questionnaires and thorough documentation. The analysis was divided based on the main variables that the study aims to assess. For the domesticity, it was found that the minimum requirement for houses in the building codes were only sufficient to place domestic items into the space, and thus needing a larger space to habituate and do their activities. A list of setting cues was also identified per economic bracket, which contains and familiar and contextualized domestic spatial information of these occupants. Flexibility exists as a coping mechanism of these low-income occupants to provide their lack of furniture and space to do specific activities. Space is found to be more multifunctional than furniture since functions are seemingly grouped together based on the limited area. Economic income and lifestyle also affect the need for flexibility since the capacity to provide a furniture or a space for a specific function becomes more tangible as the households are capable. Based on the most significant correlated values, spaces tend to be more multifunctional when they are more occupied due to the allotment of storage spaces. This in turn led more satisfaction and comfort of the users with their domestic interiors since they are able to provide more possibilities for future domestic functions. These results are vital to revolutionize design guidelines for the production of contemporary domestic spaces. Examination of domestic and flexible culture should be incorporated in design of contemporary mass housing as it places importance on the people as the prime users of the spaces. More appropriate and progressive contextualization in housing leads to better satisfaction and sustainability in housing design. Producing a more culturally sensitive, responsive domestic interiors even in the limitation of space could be used as reference to remedy contemporary spatial problems, towards an effective mass housing in the Philippines.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020